The Results of Early and Delayed Treatment of Injuries of the Extensor Tendons of the Fingers in Own Material - Anna Deskur; Zbigniew Deskur (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The aim of this study was to evaluate the results of early and delayed surgical treatment and the rehabilitation of patients with traumatic injury in zone I of the extensor tendon of the fingers II–V. 47 patients after traumatic, closed damage of the extensor tendons of the fingers II–V of the hand were treated and examined. 17 women (36.2%) and 30 men (63.8%) aged 14–80 years were included in the study. Patients with a delayed first degree damage of the extensors tendon, as well as fourth degree damage, according to the Doleyle scale qualified for surgical treatment. Surgical treatment consisted of suturing the tendon band or restoring its attachment to the phalanx bone, as well as the arthrodesis of the distal interphalangeal (DIP) joint with Kirschner wire in extension. The wire was removed after 6 weeks. Rehabilitation treatment was carried out in order to restore a full range of motion of the fingers. Patients were under constant supervision of the medical team. The examination of the patients took place before and 3 months after the surgery. The presence of the pain was assessed by means of a 10-point VAS scale (Visual Analog Scale). A goniometer was used to measure the range of motion of patient’s fingers. Crawford’s scale was used to assess the results of treatment of injuries to the extensor tendons of the fingers. The early stages of treatment to these yielded excellent results in 84.2% of patients, 14.3% good results, 17.8% of satisfactory results and 3.6% of patients had poor results. The differences in the results were not statistically significant. Further operative intervention should be considered for patients with extensive damage to the tendon of the extensor finger with a greater detachment of a fragment of phalanx bone shortly after the injury. In patients with extensive damage to the tendon of the extensor finger with greater detachment of bone fragment of phalanx further surgery in the early period after injury should be considered.